FORMULATION OF MORINGA AND EGGSHELL-BASED MOUTHWASH AS ANTIBACTERIAL AGAINST Streptococcus mutans - Pande Bagus Mahendra Putra Parmanantha; Ni Luh Putu Eka Kartika Sari; I Putu Dhananjaya Dharsila Gosa (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2025)
Background: Oral health problems such as dental caries and periodontitis are common worldwide and are mainly caused by bacterial activity, particularly Streptococcus mutans. Many commercial mouthwashes contain alcohol and chemical additives, increasing the demand for effective and safer natural alternatives.Objective: This study aimed to formulate a natural mouthwash containing Moringa oleifera leaf extract and calcium carbonate derived from eggshells, and to evaluate its antibacterial activity against Streptococcus mutans as well as its physical stability.Methods: Moringa oleifera leaf extract was prepared using the maceration method, and eggshells were analyzed for calcium carbonate content. Mouthwash formulations were produced at concentrations of 5%, 10%, and 15%. Physical evaluations included organoleptic properties, viscosity, and pH. Antibacterial activity was assessed using the well diffusion method.Results: Eggshell analysis showed a calcium carbonate content of 93.93%. All formulations met physical evaluation standards for oral care products. Antibacterial testing demonstrated inhibition zones of 6.15 mm and 7.21 mm for the 10% and 15% formulations, respectively, while no antibacterial activity was observed in the 5% formulation.Conclusions: The combination of Moringa oleifera leaf extract and eggshell-derived calcium carbonate shows potential as a natural antibacterial mouthwash against Streptococcus mutans, particularly at higher concentrations, and fulfills physical evaluation criteria.